1999
DOI: 10.1055/s-2008-1043812
|View full text |Cite
|
Sign up to set email alerts
|

Die antiinfektiöse Prophylaxe in der pädiatrischen Onkologie

Abstract: Infections in disease- and/or chemotherapy-related neutropenia are major, often emergency-type problems in the treatment of pediatric oncology patients and explain the ongoing discussion about antiinfectious prophylaxis. The different aspects of prophylaxis and an overview on the literature are presented. Antiinfectious prophylaxis in pediatric oncology includes the following issues: 1. General aspects such as information for patients and parents on neutropenia and risk of infectious diseases and indication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In our study, we found that poor handwashing habits were associated with varicella infection, consistent with the results of previous studies. 42 Hand-washing is the most direct and effective way of preventing droplet and direct transmission of varicella infection. 43 Thus, schools should offer hand-washing equipment and hand sanitizer (or soap), teach students proper hand-washing procedures, and raise their awareness on the importance of handwashing to reduce the transmission of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that poor handwashing habits were associated with varicella infection, consistent with the results of previous studies. 42 Hand-washing is the most direct and effective way of preventing droplet and direct transmission of varicella infection. 43 Thus, schools should offer hand-washing equipment and hand sanitizer (or soap), teach students proper hand-washing procedures, and raise their awareness on the importance of handwashing to reduce the transmission of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%